Increasing Wheat Productivity under Variable and Changing Climatic Conditions in West Bengal, India - Mukherjee, A.; Huda, A. K. S.; Thentu, T. L.; Banerjee, S. (International Journal of Bio-resource and Stress Management, 2017)
Wheat is the second important cereal crop after rice in West Bengal. However, its area of cultivation and production remain almost stagnant in recent years due to lower productivity of the crop. Inter seasonal climatic variability is one of the most important reasons behind it. Thus, there is a need to find out suitable management options against such climatic variability, to boost up the productivity. In this study DSSAT 4.5 model was used to simulate the potential yield of wheat for Nadia district for 30 years (1982 to 2011). The long term district wheat yield was also collected for its comparison. The attainable yield with proper agronomic management practices was collected from research experiment conducted at Bidhan Chndra Krishi Viswavidyalaya, for yield gap analysis. Wheat yield was also simulated under five number of irrigation treatments. Result revealed that the potential yield ranges from 5101 to 10128 kg ha-1 with an average of 8458 kg ha-1. The average yield produced in research field was 4151 kg ha-1 and long term average actual district yield was 2316 kg ha-1. Thus, there is ample scope to reduce the yield gap by around 80% to reach the attainable (research) yield, only through optimization of different crop management techniques. The result of the irrigation experiment showed that wheat yield increased with increase in number of irrigations. But exceptionally, three number of irrigations produced less yield than that of two numbers of irrigation due to water stress in critical crop growth period.